Target registration error minimization for minimally invasive interventions involving deformable organs. (April 2018) - Fabian, Sylwester; Spinczyk, Dominik
Graphical abstract: Highlights: Minimization of target registration error for minimally invasive intervention was achieved. Usability of thin template splines to minimize target registration error was presented. Semi-automatic real time method was implemented, which integrate specially designed marker. Abstract: Precise positioning of the target point during minimally invasive procedures is a major challenge associated with the use of image-based navigation systems. No significant dependence between fiducial registration error (FRE) and target registration error (TRE) was found. However, this investigation demonstrated the utility of using thin plate splines (TPS) and marker observation to monitor FRE during respiration to estimate target position based on the deformation field for minimally invasive procedures in deformable regions. The proposed methodology was verified via experiments involving 21 patients diagnosed with liver tumors. This method has been developed for real-time use while performing operations.